H-TEX-mediated signaling between hepatocellular carcinoma cells and macrophages and exosome-targeted therapy for hepatocellular carcinoma - Yu, Sihang; Zhou, Lei; Fu, Jiaying; Xu, Long; Liu, Buhan; Zhao, Yuanxin; Wang, Jian; Yan, Xiaoyu; Su, Jing (Frontiers in Immunology, 2022)
There is increasing evidence for the key role of the immune microenvironment in the occurrence and development of hepatocellular carcinoma. As an important component of the immune microenvironment, the polarization state and function of macrophages determine the maintenance of the immunosuppressive tumor microenvironment. Hepatocellular carcinoma tumor-derived exosomes, as information carriers, regulate the physiological state of cells in the microenvironment and control cancer progression. In this review, we focus on the role of the exosome content in disease outcomes at different stages in the progression of hepatitis B virus/hepatitis C virus-induced hepatocellular carcinoma. We also explore the mechanism by which macrophages contribute to the formation of hepatocellular carcinoma and summarize the regulation of macrophage functions by the heterogeneity of exosome loading in liver cancer. Finally, with the rise of exosome modification in immunotherapy research on hepatocellular carcinoma, we summarize the application prospects of exosome-based targeted drug delivery.